Topography-Guided Control of Local Migratory Behaviors and Protein Expression of Cancer Cells - Shin, Jung-Youn; Kim, Hong Nam; Bhang, Suk Ho; Yoon, Jeong-Kee; Suh, Kahp-Yang; Jeon, Noo Li; Kim, Byung-Soo (WILEY, 2017)
In vivo cancer cell migration and invasion are directed by biophysical guidance mechanisms such as pre-existing microtracks and basement membrane extracellular matrices. Here, this paper reports the correlation of the local migratory behavior of cancer cells and the biochemical signal expression using the topography that can guide or inhibit cell behaviors. To this end, the local apparent migration and the protein expression level are investigated with respect to the topographical feature size (flat, nanoline, and micro-line) and orientation (microline, microconcentric, and microradial) with the collectively migrating (A431) and individually migrating (MDA-MB-231 and U-87-MG) cancer cells. The results show that the migration and the protein expression of focal adhesion kinase, rho-associated protein kinase, and extracellular signal-regulated kinase are localized in the periphery of cell colony. Furthermore, the inhibition of migratory behavior at the periphery recues the protein expression, while the guidance of migration enhances the aforementioned protein expression. The results may imply the employ of biophysical inhibitory factors can help to control invasiveness of cancer cells during the progression state.
Keywords: FOCAL-ADHESION KINASE; EXTRACELLULAR-MATRIX; BREAST-CANCER; TUMOR-CELLS; INVASION; THERAPY; MICROENVIRONMENT; PROTEOLYSIS; METASTASIS; TRANSITION